PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Wulandari, Firda; Arief, Mohammad Yahya; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
Coal mining is one of the subsectors that has a major influence, its impact on the Indonesian economy. The purpose of this study is to examine the effect of Profitability, and Capital Structure in influencing Firm Value moderated by Dividend Policy. This research is explanatory research. The population in this study is a coal subsector mining company listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique is purposive sampling. Data were analyzed and hypothesis testing using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that Profitability has a significant positive effect on firm value, Capital Structure has an insignificant positive effect on firm value, Dividend Policy is unable to moderate the effect of Profitability on firm value, Dividend Policy is able to moderate the effect of Capital Structure on firm value